The Health and welfare of Australia's Aboriginal and Torres Strait Islander peoples. (AusStats electronic collection deleted, 1997)
Provides a comprehensive statistical overview, largely at the national level, of Aboriginal and Torres Strait Islander health and welfare. Topics include: mortality, morbidity, ill health, risk factors; access to and use of services; and recent developments in health and welfare information.